Pycnodysostosis with Special Emphasis on Dentofacial Characteristics - Aisha Khoja; Mubassar Fida; Attiya Shaikh (Case Reports in Dentistry, 2015)
Pycnodysostosis is an autosomal recessive disorder that manifests as osteosclerosis of the skeleton due to the defective osteoclasts mediated bone turnover. The diagnosis of this disorder is established on the basis of its characteristic features and must be differentially diagnosed with other bone disorders. Dental surgeons should be aware of the limitations and possible adverse oral complications such as osteomyelitis of bone in these patients. This will guide them in planning realistic treatment goals. This paper reports the clinical and radiographic features of pycnodysostosis with the great emphasis on its dentofacial characteristics. The aim of this case report is to give an insight into the etiology, pathogenesis, and differential diagnosis of this disorder and to prepare the dentists and maxillofacial surgeons to overcome the challenges in treating these patients.